Elbow and wrist joint loading in gymnastics: injury risk in round off technique selection - Farana, R.; Strutzenberger, G.; Exell, T.; Skypala, J.; Irwin, G. (ISBS Proceedings Archive (Michigan), 2017)
The aim of the current study was to investigate key elbow and wrist joint injury risk factors during different round-off (RO) techniques performed by young female artistic gymnasts. Ten active female gymnasts performed 30 successful trials of RO from a hurdle step with three different hand positions (parallel (10), T-shape (10) and reverse (10)). Synchronized kinematic and kinetic data were collected for each trial. One-way ANOVA and effect-size statistics determined differences between each hand position. Significant differences (p<0.05 and large ES (>0.8) among hand positions were found for peak VGRF, peak elbow and wrist compression force, and elbow internal adduction moment. Decrease in VGFR, elbow and wrist joint kinetics indicated that the T-shape technique may prevent elbow and wrist joint complex and reduces potential of injuries.